Estudo do potencial farmacoquímico de Kalanchoe brasiliensis Cambess.: dimalato de kalanchosina como fitofármaco antinocicptivo - Mayorga, Oscar Alejandro Santos (2024)
Kalanchoe brasiliensis Cambess. (Crassulaceae) is a plant native to Brazil, popularly known as "white coirama", "saião", "folha da costa", among others. Recently, it has been of increasing interest due to its anti-inflammatory and anti-ulcer properties. Among the chemical substances with pharmacological potential, the flavonoids stand out, especially those derived from patuletin, as well as kalanchosine dimalate (KMC), a bis-dimer (γ-hydroxy-β-amino acid). In this context, the present study aims to perform an in vivo and in silico pharmacochemical study of the freeze-dried aqueous leaves extract of K. brasiliensis (ELKB) and KMC, focusing on the evaluation of the antinociceptive activity, with the aim of obtaining a phytopharmaceutical. The methodology used in this study was divided into four phases. In phase I, the phytochemical and chromatographic analysis of ELKB was performed using Ultra Efficiency Liquid Chromatography coupled with Mass Detector (CLUE-EM). In Phase II, the physicochemical properties of KMC were evaluated by total ash content, solubility, thermogravimetric and spectrophotometric analysis tests. In Phase II, the physico-chemical properties of KMC were evaluated by total ash content, solubility, thermogravimetric and spectrophotometric analyzes. The identification of KMC was carried out using infrared spectrometry (IR) and nuclear magnetic resonance (NMR). In phase III, the orofacial antinociceptive activity and the mechanism of action of ELKB and KMC in adult zebrafish (D. rerio) were investigated in vivo. Finally, an in silico study of antinociceptive activity was conducted in phase IV using molecular coupling of ligands such as the main compound of ELKB (patuletin 3-O-α-L-rhamnopyranosyl-7-O-α-L -rhamnopyranoside - ELKB-P37R) and KMC to TRPV1, NMDA and ASIC receptors. In addition, the ADME values of the ligands were calculated to obtain a comprehensive understanding of their pharmacokinetic properties. The yield obtained was 2.25% for ELKB and 1.5% for KMC. Chemical analysis by CLUE-EM confirmed the presence of patuletin-derived flavonoids in ELKB. The structure of KMC was confirmed by IR and NMR results. KMC was soluble only in distilled water, the process being facilitated by the addition of hydrochloric acid and the removal of calcium from the precipitate. The results of the nociception test showed that ELKB and KMC did not affect the zebrafish's locomotor system. In addition, there was a significant reduction in orofacial nociceptive behavior elicited by capsaicin, acid saline and glutamate. However, no antinociceptive activity was observed when cinnamaldehyde, menthol and acid saline were administered. The mechanism of action suggests that ELKB and KMC interact with TRPV1 and NMDA receptors. Molecular coupling analysis revealed a number of interactions between the tested molecules and TRPV1, ASIC and NMDA receptors. From a pharmacokinetic point of view, the KMC molecule has an advantage, although the ELKB-P73R molecule has a higher affinity for the receptors in the in silico interactions. The research results show that both ELKB and KMC have an antinociceptive effect by preventing the activation of TRPV1, ASIC and NMDA receptors. In this sense, it was concluded that the compounds studied proved to be potential candidates for the development of phytopharmaceuticals, especially KMC, contributing to the production chain of new drugs for the treatment of pain.